Agreement to built a new structure telco project and permission to work / Mohamad Hazazi Hazran Mohd Rizal - Mohd Rizal, Mohamad Hazazi Hazran (Universiti Teknologi MARA, Perak, 2022)
Telecommunication is the transmission of information by various types of technologies over wire, radio, optical, or other electromagnetic systems according to Wikipedia. Today, telecommunication is widespread and devices that assist the process, such as the television, radio and telephone, are common in many parts of the world. There is also a vast array of networks that connect these devices, including computer networks, public telephone networks, radio networks and television networks.